Mitochondrial genome of Chrysochares punctatus (Coleoptera: Chrysomelidae: Eumolpinae) and phylogenetic analysis. Issue 1 (2nd January 2020) - Feng, Run-Qiu; Zhang, Li-Jun; Li, Min; Liu, Jia; Wen, Chun-Li; Yuan, Ming-Long
Abstract: Here, we determined the nearly complete mitochondrial genome (mitogenome) of Chrysochares punctatus (Coleoptera: Chrysomelidae: Eumolpinae), an important insect pest on Apocynum venetum in Northwestern China. This mitogenome was 14, 451 bp long, encoding 13 protein-coding genes (PCGs), 21 transfer RNA genes (tRNAs), and 2 ribosomal RNA genes. The C. punctatus mitogenome presented an A + T content of 75.11%, with a positive AT-skew (0.064) and a negative GC-skew (−0.192). Ten PCGs started with a typical ATN codon, whereas the remaining three PCGs started with AAC ( cox1 ) and TTG ( nad1 and nad2 ). All tRNAs had a typical secondary cloverleaf structure, except for trnS1 which lacked the dihydrouridine arm. Bayesian phylogenetic analysis based on the nucleotide sequences of 13 PCGs recovered a phylogeny within Chrysomelidae: (((Chrysomelinae + Galerucinae), (((Eumolpinae, Lamprosomatinae), Cassidinae), Criocerinae)), Bruchinae).